Aplikasi Integral dalam Menghitung Volume dan Panjang Busur pada Design Cone Es Krim Berbentuk Kelopak Bunga - Asni Al Amini; Kenjo Oktaviano Damanik; Monica Triyuni Sinaga; Riby Tamara; Zahra Marsanda Mahisa; Suvriadi Panggabean (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to apply integral calculus methods to calculate the volume and arc length of an ice cream cone design shaped like a flower petal. The cone design is modeled using a quadratic function derived from three reference points on the petal curve. Using the solid of revolution method around the y-axis, the calculated petal volume is 150.8 cm³, and the arc length is 7.14 cm. The results demonstrate that calculus-based modeling supports efficient material usage while enhancing aesthetic and functional aspects of packaging. This research highlights the connection between mathematical concepts and practical product design in the food industry